Li-Fi the future of Vehicular Ad hoc Networks - M S, Diyar Khairi; Berqia, Amine (Discoveries in Agriculture and Food Sciences, 2015)
VANET is a set of vehicles moving on the road, equipped with communication capabilities among one to another and with Road Side Units using wireless technologies such as Wi-Fi or WiMAX. The number of possible applications of VANETs is expanding. In addition to safety applications, vehicles are foreseen to support entertainment applications such as peer-to peer applications and Internet connectivity applications. For all this, most mobile data traffic is consumed. Light fidelity (Li-Fi) which is related to visible light communication (VLC) offers many key advantages, and effective solutions. This paper presents some advantages that can improve performance of VANETs by using Li-Fi which is interesting to reach high speed data communication between vehicles.